Discursive Reconfiguration or New Identity? A Foucauldian Bibliometric Analysis of Corporate Accountability Research - Dwiyani Sudaryanti; Mohamad Bastomi; Siti Afiqah Zainuddin (Jurnal Ilmiah Akuntansi, 2026)
This study examines the discursive evolution of corporate accountability research from 2000 to 2025 through a Foucauldian perspective. It integrates temporal bibliometric analysis with Foucauldian genealogy to investigate how dominant concepts, theoretical frameworks, and power–knowledge relations have shaped changing regimes of truth in the field. The dataset comprises 6,559 English-language journal articles indexed in Scopus within the business, management, and accounting subject area. Keyword frequencies and co-occurrence patterns were analyzed using Python to identify temporal shifts, discursive ruptures, and changes in the relationships among corporate social responsibility, sustainability, ethics, financial performance, and environmental, social, and governance concepts. The findings indicate three broad transformations. Corporate accountability research initially emphasized ethics, philanthropy, and stakeholder responsibility; it subsequently became more theoretically structured through stakeholder, institutional, and legitimacy perspectives; and, from 2010 onward, it increasingly adopted an economic and performance-oriented rationality. The recent rise of ESG further reflects a movement toward measurable, investor-oriented, and financially interpretable forms of accountability. These patterns suggest that the evolution of corporate accountability research is not merely a linear expansion of ethical responsibility but a discursive reconfiguration shaped by changing academic, institutional, and capital-market priorities. The study contributes by demonstrating how bibliometric evidence can support—but not independently establish—a Foucauldian interpretation of knowledge production in accounting research.